Cryptogenic Stroke: A Challenge in Diagnosis and Management - Purwowiyoto, Sidhi Laksono; Setianto, Budhi; Panindhita, Gea; Halomoan, Reynaldo; Wiryawan, I Nyoman (The Indonesian Heart Association, 2021)
Ischemic stroke is responsible for 85% of all stroke globally. However, the etiology of around a quarter of ischemic stroke are undetermined, this is called cryptogenic stroke. This kind of stroke affects younger population. Several mechanism are associated with the incidence of cryptogenic stroke such as paroxysmal atrial fibrillation, patent foramen ovale, atherosclerosis, and atrial cardiopathy. Despite many advanced knowledge on stroke generally, cryptogenic stroke is still a challenge in clinical settings. To understand more about cryptogenic stroke, a new term of embolic strokes of undetermined source (ESUS) is proposed and may need a specific workup. Specific workup aims to detect any silent risk factors and also to evaluate the cardiac structure. The term of ESUS also leads to the understanding that cryptogenic stroke is highly related to embolic mechanism and anticoagulation administration might benefit the patients. However, the result of several recent studies showed that anticoagulant was not superior to antiplatelet, and antiplatelet is still the preferred treatment. Studies on PFO closure also shows different result, but the majority of the trials showed benefit of PFO closure in reducing the risk of stroke recurrence.